Beiträge zur Taxonomie und Faunistik der paläarktischen Trauermücken (Diptera, Sciaridae). Teil II. - Die Sciaridae des Museums für Naturkunde der Humboldt-Universität zu Berlin. - Menzel, Frank (Contributions to Entomology = Beiträge zur Entomologie, 1992)
The collections of Sciaridae (Insecta: Diptera) of the Zoologisches Museum der Humboldt-Universität are listed. In total, this collection consists of 54 species in 13 genera and includes the types of 6 species from the Palaearctic region which are redescribed and figured. In addition, 3 new synonymies and 3 new combinations are recognised and several interesting records for the European fauna are presented.Nomenclatural Actskairensis (Becker, 1903) (Bradysia), comb. n. hitherto Sciara kairensisregularis (Lengersdorf, 1934) (Bradysia), Lectotype described as Neosciara regularisgracilicornis Lengersdorf, 1926 (Corynoptera), syn. n. of Epidapus (Epidapus) microthorax (Börner, 1903)titan Frey, 1948 (Epidapus), syn. n. of Epidapus (Epidapus) schillei (Börner, 1903)subterranea (Märkel, 1844) (Lycoriella (Lycoriella)), Lectotype; comb. n. hitherto Sciara subterranealackschewitzi (Lengersdorf, 1934) (Sciara), Lectotype; comb. n. hitherto Lycoria lackschewitzimendax Tuomikoski, 1960 (Sciara), syn. n. of Sciara lackschewitzi (Lengersdorf, 1934)